In Vivo Analysis of Troponin C Knock-In (A8V) Mice: Evidence that TNNC1 Is a Hypertrophic Cardiomyopathy Susceptibility Gene. (October 2015) - Martins, Adriano S.; Parvatiyar, Michelle S.; Feng, Han-Zhong; Bos, J. Martijn; Gonzalez-Martinez, David; Vukmirovic, Milica; Turna, Rajdeep S.; Sanchez-Gonzalez, Marcos A.; Badger, Crystal-Dawn; Zorio, Diego A.R.; Singh, Rakesh K.; Wang, Yingcai; et al.
Abstract : Background—: Mutations in thin-filament proteins have been linked to hypertrophic cardiomyopathy, but it has never been demonstrated that variants identified in the TNNC1 (gene encoding troponin C) can evoke cardiac remodeling in vivo. The goal of this study was to determine whether TNNC1 can be categorized as an hypertrophic cardiomyopathy susceptibility gene, such that a mouse model can recapitulate the clinical presentation of the proband. Methods and Results—: The TNNC1-A8V proband diagnosed with severe obstructive hypertrophic cardiomyopathy at 34 years of age exhibited mild-to-moderate thickening in left and right ventricular walls, decreased left ventricular dimensions, left atrial enlargement, and hyperdynamic left ventricular systolic function. Genetically engineered knock-in (KI) mice containing the A8V mutation (heterozygote=KI-TnC-A8V +/− ; homozygote=KI-TnC-A8V +/+ ) were characterized by echocardiography and pressure–volume studies. Three-month-old KI-TnC-A8V +/+ mice displayed decreased ventricular dimensions, mild diastolic dysfunction, and enhanced systolic function, whereas KI-TnC-A8V +/− mice displayed cardiac restriction at 14 months of age. KI hearts exhibited atrial enlargement, papillary muscle hypertrophy, and fibrosis. Liquid chromatography–mass spectroscopy was used to determine incorporation of mutant cardiac troponin C (≈21%) into the KI-TnC-A8V +/− cardiac myofilament. Reduced diastolic sarcomeric length, increased shortening, and prolonged Ca 2+ and contractile transients were recorded in intact KI-TnC-A8V +/− and KI-TnC-A8V +/+ cardiomyocytes. Ca 2+ sensitivity of contraction in skinned fibers increased with mutant gene dose: KI-TnC-A8V +/+ >KI-TnC-A8V +/− >wild-type, whereas KI-TnC-A8V +/+ relaxed more slowly on flash photolysis of diazo-2. Conclusions—: The TNNC1-A8V mutant increases the Ca 2+ -binding affinity of the thin filament and elicits changes in Ca 2+ homeostasis and cellular remodeling, which leads to diastolic dysfunction. These in vivo alterations further implicate the role of TNNC1 mutations in the development of cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.